Effect of Work Environment and Leadership Style on Employee Performance Through Motivation as an Intervening Variable (Empirical Study of PT Permodalan Nasional Madani) - Irawan, Hengki; Safaria, Siti (PT FORMOSA CENDEKIA GLOBAL, 2024)
The goal of this study is to ascertain how the work environment affects employee performance, how leadership style affects employee performance, how the work environment affects motivation, how leadership style affects motivation, how the work environment affects performance through motivation, and how leadership style affects performance through motivation. This study uses primary data and is classified as a quantitative study. 210 workers at the Padang location of PT PNM (Persero) are the study's subjects. The study's findings are: A supportive work environment is the primary factor in raising employee motivation, an effective leadership style can significantly increase employee motivation, a conducive work environment, and a good leadership style all significantly contribute to performance improvementbeen demonstrated to have a substantial impact on performance in this study, motivation does not significantly mediate the relationship between leadership style and performance, nor does it significantly mediate the relationship between work environment and performance